Pengaruh Variasi Arus Las SMAW Terhadap Uji Tarik dan Uji Kekerasan Serta Struktur Mikro Pada Bahan ST 37 - Surahman, Andika; Mufarida, Nely Ana; Kosjoko, Kosjoko (Indonesian Journal Publisher, 2023)
This research aims to determine the effect of variations in welding currents of 90A, 100A, and 110A on SMAW bases on the material in the tensile, hardness, and microstructure tests. This research uses ST37 low carbon steel and uses E6013 electrodes with a diameter of 3.2 mm, followed by making specimens for testing. After that, the welding process is carried out and then testing continues. In the test, the following results were obtained: The strength value of the welded material with tensile testing was obtained with the highest results at a current variation of 110A with Yp 27.33 Mpa, Max 36.47 Mpa, Break 31.08 Mpa. Because the highest pearlite microstructure value is obtained in the 110A variation. And the lowest value occurred in the welded material of variation 90A with Yp 25.48 Mpa, Max 26.86 Mpa, Break 12.33 Mpa. Because the lowest pearlite microstructure value is obtained in the 90A variation. while the comparison of the level of hardness in ST 37 carbon steel with varying welding currents ranging from 90A, 100A, and 110A has an average hardness value of 168 VHN for welding with a current of 90A for welding with a current of 100A the average hardness value is 177 VHN and finally in welding current 110A the average hardness value is 191 VHN. The hardness level of the ST 37 carbon steel specimen was the highest at a welding current of 110A, with a tensile strength test result of 36.47 MPa. And from the results of observing photos of the microstructure using the point count method, the highest percentage of pearlite was in the welding material variation 110A so the tensile strength value was higher.